Effect of manufacturing parameters on TBC systems cyclic oxidation lifetime - Chirivi, Laura (Cranfield University, 2011)
Aero-gas turbine engines have to meet reliability, durability and fuel e ciency requirements. High turbine inlet temperatures may contribute to minimise fuel consumption and, in turn, environmental impact of the engine. Over the past few years, new designs and engine optimisation have allowed increase of such temperatures at a rate of 15 C per year, with maximum operating temperatures currently exceeding 1650 C. Ceramic coatings (also known as Thermal Barrier Coatings or TBCs) in conjunction with advanced cooling technologies are adopted to protect stator vanes and high pressure turbine blades from excessive thermal loads. Nevertheless, even with these protections in place, such components may experience a continuous service temperature of 1050 C, and peak temperatures as high as 1200 C. Therefore, it is vital that engine rotating components are able to maintain their mechanical properties at high temperature, while being able to withstand thermal loads and having su cient oxidation resistance to preserve the integrity of the ceramic coating, and eventually reaching desired component lives. Such strict requirements can be met with the use of complex Thermal Barrier Coat- ing systems or TBC systems; these consist of a nickel-based superalloy component which is rst coated with an environmental resistant layer (identi ed as bond coat ) and then with a ceramic coating. As its name suggests, the bond coat must not only protect the metallic substrate against oxidation and/or corrosion but must also provide su - cient bonding of the ceramic top layer to the metallic substrate. This goal is achieved through the formation of a further layer between the bond coat and the ceramic. In gas turbine applications, such a layer (identi ed as Thermally Grown Oxide or TGO) is an alumina scale which is the result of the bond coat oxidation during the ceramic deposition. During engine service, several time and cycle related phenomena occur within the TBC system which eventually lead the system to failure by spallation of the top coat.Aero-gas turbine engines have to meet reliability, durability and fuel e ciency requirements. High turbine inlet temperatures may contribute to minimise fuel consumption and, in turn, environmental impact of the engine. Over the past few years, new designs and engine optimisation have allowed increase of such temperatures at a rate of 15 C per year, with maximum operating temperatures currently exceeding 1650 C. Ceramic coatings (also known as Thermal Barrier Coatings or TBCs) in conjunction with advanced cooling technologies are adopted to protect stator vanes and high pressure turbine blades from excessive thermal loads. Nevertheless, even with these protections in place, such components may experience a continuous service temperature of 1050 C, and peak temperatures as high as 1200 C. Therefore, it is vital that engine rotating components are able to maintain their mechanical properties at high temperature, while being able to withstand thermal loads and having su cient oxidation resistance to preserve the integrity of the ceramic coating, and eventually reaching desired component lives. Such strict requirements can be met with the use of complex Thermal Barrier Coat- ing systems or TBC systems; these consist of a nickel-based superalloy component which is rst coated with an environmental resistant layer (identi ed as bond coat ) and then with a ceramic coating. As its name suggests, the bond coat must not only protect the metallic substrate against oxidation and/or corrosion but must also provide su - cient bonding of the ceramic top layer to the metallic substrate. This goal is achieved through the formation of a further layer between the bond coat and the ceramic. In gas turbine applications, such a layer (identi ed as Thermally Grown Oxide or TGO) is an alumina scale which is the result of the bond coat oxidation during the ceramic deposition. During engine service, several time and cycle related phenomena occur within the TBC system which eventually lead the system to failure by spallation of the top coat.Aero-gas turbine engines have to meet reliability, durability and fuel e ciency requirements. High turbine inlet temperatures may contribute to minimise fuel consumption and, in turn, environmental impact of the engine. Over the past few years, new designs and engine optimisation have allowed increase of such temperatures at a rate of 15 C per year, with maximum operating temperatures currently exceeding 1650 C. Ceramic coatings (also known as Thermal Barrier Coatings or TBCs) in conjunction with advanced cooling technologies are adopted to protect stator vanes and high pressure turbine blades from excessive thermal loads. Nevertheless, even with these protections in place, such components may experience a continuous service temperature of 1050 C, and peak temperatures as high as 1200 C. Therefore, it is vital that engine rotating components are able to maintain their mechanical properties at high temperature, while being able to withstand thermal loads and having su cient oxidation resistance to preserve the integrity of the ceramic coating, and eventually reaching desired component lives. Such strict requirements can be met with the use of complex Thermal Barrier Coat- ing systems or TBC systems; these consist of a nickel-based superalloy component which is rst coated with an environmental resistant layer (identi ed as bond coat ) and then with a ceramic coating. As its name suggests, the bond coat must not only protect the metallic substrate against oxidation and/or corrosion but must also provide su - cient bonding of the ceramic top layer to the metallic substrate. This goal is achieved through the formation of a further layer between the bond coat and the ceramic. In gas turbine applications, such a layer (identi ed as Thermally Grown Oxide or TGO) is an alumina scale which is the result of the bond coat oxidation during the ceramic deposition. During engine service, several time and cycle related phenomena occur within the TBC system which eventually lead the system to failure by spallation of the top coat.This may have catastrophic consequences as the uncoated component would face temperatures higher than the melting point of the constituent metal. This is avoided by strict maintenance regimes based on the minimum expected life of the coating. While essential for safeguarding the aircraft, this approach prevents the TBC systems from being used to their full potential. This study investigates possible optimisation methods of the manufacturing process of TBC systems, with the aim of improving reproducibility in terms of time to failure, thereby extending their minimum life expectancy and reliability. Two di erent types of TBC systems are studied: a TBC system with a Platinum-di used bond coat and a TBC system with a Platinum-modi ed aluminide bond coat. The work focuses on the e ects due to modi cation of process parameters (varied within industrially accepted range) on the TBC systems lifetime in laboratory scale cyclic oxidation tests. Experimental results show that accurate monitoring of the metal substrate surface nish as well as of the Pt layer morphology and ceramic deposition temperature may result in a dramatic improvement in life expectancy of the system, up to sevenfold when compared to control samples, or threefold if compared to commercial coatings.